(untitled) (Texas Journal of Medical Science, 2023)
We have studied texture and sites of pulmonary trunk in children (from the birth to 12 years of life). Experiments were carried out on 55 children’s corpses. The following results were obtained: pulmonary trunk develops continuously and asynchronously: rapid growth process develops in children of an early age, diameter of pulmonary trunk increases from the first days of its existence and subsequently develops in its length